The Influence of Experience on Online Shopping Familiarity and Purchase Intention - Huaiqin Li; 임승희; 홍진환 (무역연구, 16(5), 2020)
Purpose This study clarifies the mechanisms that underlie the experiences that affect Chinese consumers’ purchase intentions. The purpose of this study is to examine which type of consumer experience affects online shopping website familiarity, and how website familiarity affects trust and purchase intention. In particular, this study distinguishes between subjective and objective familiarity in an online shopping context. Design/Methodology/Approach Chinese online shopping consumers are surveyed by questionnaire, and 317 surveys were used in the empirical analysis with a structural equation model. Findings The results show that website usage and advertising are the most influential predictors of consumers’ website familiarity, particularly subjective familiarity, while electronic word of mouth (E-WOM) only affects objective familiarity. In addition, objective familiarity is positively related to trust, but subjective familiarity is not. This indicates that consumers actually know and trust more. Research Implications This study provides important insights into experience, which was found to be the most influential predictor of a consumer’s level of familiarity. This highlights the differences between what consumers think they know and what they actually know about a website. This study also built a valid and reliable scale for measuring familiarity in an online shopping market, and developed a theoretical framework identifying how direct experiences and indirect experiences influence familiarity. KCI Citation Count: 1